2005
DOI: 10.1159/000085865
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Different Marigold <i>(Calendula officinalis L.)</i> and Rosemary Cream Preparations against Sodium-Lauryl-Sulfate-Induced Irritant Contact Dermatitis

Abstract: In the present study, we evaluated the protective action of cream preparations containing seven different types of marigold and rosemary extracts in vivo in healthy volunteers with experimentally induced irritant contact dermatitis (ICD). Marigold and rosemary extracts in base cream DAC (Deutscher Arzneimittel-Codex = German Pharmaceutical Codex) were tested in a 4-day repetitive irritation test using sodium lauryl sulfate. The effect was evaluated visually and quantified by noninvasive bioengineering methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 29 publications
(14 reference statements)
0
15
1
Order By: Relevance
“…While we did not observe any inhibition with calendula oil, other studies have documented its positive contribution to wound healing [27-30]. Calendula is associated with lymphocyte activation [15], angiogenesis [30], and alleviation of irritations [31], so it is plausible that its role in healing is due primarily to immune modulation and stimulation of tissue repair rather than antimicrobial activity.…”
Section: Resultscontrasting
confidence: 48%
“…While we did not observe any inhibition with calendula oil, other studies have documented its positive contribution to wound healing [27-30]. Calendula is associated with lymphocyte activation [15], angiogenesis [30], and alleviation of irritations [31], so it is plausible that its role in healing is due primarily to immune modulation and stimulation of tissue repair rather than antimicrobial activity.…”
Section: Resultscontrasting
confidence: 48%
“…In particular, attention has been drawn to faradiol monoester and unesterfied faradiol, whose anti-inflammatory activities have been found to be of the same order of magnitude as that of indomethacin [18] . It has been claimed that these compounds play an important role in the anti-inflammatory properties of C. officinalis extracts [18,27,29,31,33] , and our chemical analysis of the investigated extract revealed the presence of unesterified faradiol and mainly lauryl, myristoyl and palmitoyl monoesters, which were the most abundant components.…”
Section: Discussionmentioning
confidence: 66%
“…The anti-inflammatory effects of C. officinalis extracts have been documented for topical applications using the croton oil-induced edema of the mouse ear test [18,[29][30][31] . A wound-healing activity [32] and protective effects in irritant contact dermatitis and in acute dermatitis during irradiation have also been reported [33,34] . A concentration-dependent reduction in lipid peroxidation has been observed in vitro [16,17] and in vivo tests of the inhibition of superoxide generation in mouse macrophages [17] , and by an increase in catalase activity after oral administration [17] .…”
Section: Discussionmentioning
confidence: 99%
“…(1996), showed positive preliminary results for the administration of calendula ointment in the treatment of venous leg ulcers [47]. It has been demonstrated that calendula as a cream preparation protected skin from irritant contact dermatitis caused by exposure to sodium lauryl sulfate [48]. And as earlier mentioned, calendula was highly effective in the prevention of acute dermatitis in patients with cancer undergoing postoperative irradiation [12].…”
Section: Discussionmentioning
confidence: 99%